The Structure of Adamantane Clusters: Atomistic vs. Coarse-Grained Predictions From Global Optimization - Hernández-Rojas, Javier; Calvo, Florent (Frontiers in Chemistry, 2019)
Candidate structures for the global minima of adamantane clusters, (C$_{10}$H$_{16}$)$_N$, are presented. Based on a rigid model for individual molecules with atom-atom pairwise interactions that include Lennard-Jones and Coulomb contributions, low-energy structures were obtained up to $N=42$ using the basin-hopping method. The results indicate that adamantane clusters initially grow accordingly with an icosahedral packing scheme, followed above $N=13$ by a structural transition toward face-centered cubic structures. The special stabilities obtained at $N=13$, $19$, and $38$ are consistent with these two structural families, and agree with recent mass spectrometry measurements on cationic adamantane clusters. Coarse-graining the intermolecular potential by averaging over all posible orientations only partially confirm the all-atom results, the magic numbers at $13$ and $38$ being preserved. However, the details near the structural transition are not captured well, because despite their high symmetry the adamantane molecules are still rather anisotropic.